KINERJA ROOM BOY PANGERAN HOTEL PEKANBARU - Aprinaldi, Ilegsias Wendy; Sulistyani, Andri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2019)
Hotel Pangeran is a hotel located in Jalan Sudirman Pekanbaru Prince Hotel is a hotel located in the city center so it is a strategic location in the city of Pekanbaru. The purpose of this research is to know the performance of Room Boy Hotel Prince Pekanbaru and this research use qualitative with a descriptive approach to know the problems that exist in the room boy prince. Respondents numbered 5 people. The data collection technique uses observations, interviews, Documentation. This shows that the performance of room boy Prince in terms of quality of 100%, quantity 100%, time 79%, teamwork 80% in performance implementation Room boy not yet in accordance with the applicable SOP, those things determine how high the performance room The Pangeran Hotel Keywords: room boy, performance, house keeping, hotel